Institutional constraints and the translation of college aspirations into intentions—Evidence from a factorial survey. (December 2016) - Finger, Claudia
Highlights: I analyze in what way institutional opportunities and constraints in higher education influence whether high school students' college aspirations translate into equally high intentions. Applying a factorial survey enables me to measure contextualized and constrained educational intentions more directly than individual survey questions. The findings show that institutional opportunities and constraints influence whether college aspirations also translate into college intentions; distance between students' place of residence and the university city is the strongest constraint for prospective students. Whereas social inequality can be observed with regard to the strength of college intentions, the influence of institutional opportunities and constraints does not vary strongly between students from different social backgrounds. Abstract: This article examines under which conditions high school students' college aspirations (unconstrained wishes) translate into (constrained) college intentions. Drawing on the Wisconsin model of status attainment and sociological rational choice theory, it is argued that—while educational aspirations are mainly the result of socialization processes within families and schools—educational intentions are constrained by institutional opportunities and barriers emerging from the higher education system, which might influence students from different social backgrounds in different ways. The focus lies on four institutional characteristics of German higher education institutions—namely geographical distance, reputation, selection procedures and the information provided by colleges. Methodologically, I draw on a factorial survey on application intentions for college programs that is integrated in a survey of Berlin high school students who indicated an aspiration to attend college one year before graduating. The findings suggest that distance from home is an especially strong constraint on college application intentions. The effects of the institutional dimensions, however, rarely differ for students from different social backgrounds. Nevertheless, social background differences can be observed regarding the overall strength of application intentions indicating that socially advantaged students feel generally less constrained by the institutional characteristics presented to them. The implications of these findings are discussed.